Beauty Consultant: Mary Kay / Azlin Peter - Peter, Azlin (2022)
Every firm begins with a set of a clear objectives and goals in order to meet a set of requirements. As a result, every entrepreneur will begin their business by identifying and implementing business opportunities. The availability of business opportunities aids us in identifying requirements, developing appropriate solutions and devising strategies to benefit on those opportunities. I've decided to be a MARY KAY Beauty Consultant which distributes cosmetics products for my business opportunity . The reason I choose this company because MARY KAY is a very trustworthy and Top Global number 3 compan^Hrtfie world. These products are well known among men and women.